Universal Digital Probe Electrometer for Testing Semiconductor Wafers - A. L. Zharin; U. A. Mikitsevich; A. I. Svistun; K. U. Pantsialeyeu (Приборы и методы измерений)
Non-contact electrical methods are widely used for research and control of semiconductor wafers. The methods are usually based on surface potential measurement (CPD) in combination with illumination and/or deposition of charges on the sample using a corona discharge, and are also based on the measurement of surface photo-emf. By photo-EMF (SPV) it is possible to determine the lifetime of minor charge carriers, their diffusion length and detect traces of heavy metals on the surface. In addition, using photo-EMF it is possible to determine the surface resistance of the plate, some parameters of the dielectric layer on the surface and barrier photo-EMF (JPV). Electrical performance results reflect the influence of near-surface characteristics on the final performance of devices. The aim of the work was to develop a universal digital probe electrometer that implements various non-contact electrical methods for analyzing semiconductor wafers, in which the change in operating modes and configuration, transmission of the received data, remote testing and calibration are carried out via digital local control channels. This paper describes a universal digital probe electrometer developed by the authors, which implements the above-described non-contact electrical methods for analyzing semiconductor wafers (CPD, SPV and JPV), in which the change in operating modes and configuration, transmission of the received data, remote testing and calibration are carried out via digital local control channels. Due to their high speed, electrical characterization methods are suitable for inspecting semiconductor wafers during production. The results of testing the developed probe electrometer in CPD, SPV and JPV modes are presented, which reflect the effectiveness of the proposed approaches.